IDENTIFICATION OF NOVEL DRUG TARGETS AGAINST CAMPYLOBACTERJEJUNI USING METABOLIC NETWORK ANALYSIS - ANUKRITI VERMA; BHAWNA RATHI; SHIVANI SHARDA (International Journal of Pharma and Bio Sciences, 2016)
Campylobacter jejuni is a gram- negative bacteria that is known to cause Guillain-Barre syndrome (GBS) that can lead to paralysis of the human body. It is necessary to find its essential drug targets in order to curb and control GBS. The large amount of genomic/proteomic data in collaboration with systems biology approach can lead to the identification of potential and putative pathogenic drug targets. The combination of subtractive proteomics approach and metabolic network reconstruction was employed for finding novel targets in Campylobacter jejuni. Our study revealed that this pathogenic microorganism consists of 228 essential genes present in database of essential genes that are non- paralogous. 151 sequences were non- homologous to Homo sapiens. The KO numbers of 94 essential genes could be retrieved out of which 36 genes were involved in metabolism. The metabolic network of these sequences was created and simulation analysis of this network was performed that produced 6 essential reactions including 2 proteins UDP-N-acetylmuramate dehydrogenase encoding murB gene and 4-hydroxy-3-methylbut-2-enyl diphosphate reductase encoding ispH and lytB genes. These can be used as prospective drug targets.